Spectral qualities of light: effects on human perception and the human visual system - Wheeler, Collin, P. (Kansas State University, 2016)
By definition, light is a metric created solely for the visual response of human beings. As a result, nearly every lighting metric is weighted to accurately depict human responses. The first human visual response function was adopted in 1924 by the CIE, V(λ), and is still the primary function weighting for all other lighting metrics. However, V(λ) has obvious limitations, one being that it only includes contributions from long- and medium-wavelength photoreceptors. Therefore, V(λ) cannot accurately provide indication to visual acuity (VA). Because vision is a sense that humans rely so heavily on, causes for optimal vision are valued in order to create artificially lit spaces that emulate qualities on which the human visual systems thrives. One factor of VA is pupillary diameter, which is dictated by many factors ranging from light spectra to emotional states. The formula P(S/P)ˣ was derived to predict how average pupil size is influenced by general light spectra. Generally, the smaller the pupil, the greater VA. Per the formula, increased scotopic (V’(λ)) lumens result in smaller pupils. A rearrangement of the P(S/P)ˣ formula provided a mathematical means for quantifying an illuminance reduction, later established by the IES as Equivalent Visual Efficiency (EVE) Factors. In theory, acceptable reduced illuminance levels result in less energy consumed. Not everyone saw the benefits of spectrally enhanced lighting though; the practicality, extent of application, and actual preference of light sources that allow the usage of EVE Factors remain a polarized subject. Intrinsically photosensitive retinal ganglion cells (ipRGC) were discovered in 2002, after the derivation of the P(S/P)ˣ formula. However, they are known to play a role in pupil size. Emotional and ipRGC contributions to pupil size are ambiguities that prove a weak point in the argument for reducing illuminance levels. Overall, this report compiles and analyzes research over the past century. Initially, background information on light, metrics, light sources, and human biology is introduced. Then specifics on human vision follow. Arguments for and against IES EVE Factors are presented, and ultimately, a recommendation is provided on the implementation of EVE Factors. The Appendix houses example EVE calculations and values.
Keywords: Spectra; Pupil; Vision; Energy; IESLight